Reconsidering 'Globalisation': Judicial Reform in the Philippines - R. Hunter (Law Text Culture, 2002)
Various commentators have identified the development of 'globalised' law--Western and neo-liberal in origin--produced by global economic imperatives, and particularly under the demands of the International Monetary Fund (IMF) and the World Bank. For example, David Trubek et al note that 'Legal fields have become important assets in the global competition for investment', and that the particular legal configurations perceived as necessary for successful competition include '"modern" laws, "efficient" courts, and "business oriented" legal professions' (Trubek et al 1994: 477). Boaventura de Sousa Santos observes the hierarchy of legal systems being reproduced in 'the successful globalization of a given [i.e. Western] localism' (Santos 1995: 263). And Peter Fitzpatrick critiques the loan conditions imposed by the IMF and the World Bank, derived from the Western nations that donate funds rather than the 'developing' nations that receive them, which all ultimately promote a neo-liberal agenda involving the supremacy of the free market and a limited role for the nation state (Fitzpatrick 2001: 213). In addition to explicit economic prescriptions of liberalisation, deregulation and privatisation, these loan conditions include political prescriptions of democracy, human rights and the rule of law. In particular, Fitzpatrick remarks upon the 'immense material commitment ... to promoting the rule of law and the "transplanting" or "reception" of occidental laws, especially those of a commercial variety' (Fitzpatrick 2001:214).